Supply chain management and industry 4.0: a theoretical approach - Kunrath, Tobias Leonardo; Dresch, Aline; Veit, Douglas Rafael (Brazilian Journal of Operations & Production Management, 2022)
Goal: The purpose of this study is to analyze how the elements of industry 4.0 relate to Supply Chain Management (SCM) by identifying mechanisms that promote or include these elements in the supply chain. The elements of industry 4.0 relate to the basic processes of Supply Chain Operations Reference (SCOR) when considering the literature on the subject. Design / Methodology / Approach: A systematic literature review was performed, and 293 articles were selected and analyzed. Content analyses were conducted to identify the main contributions of elements in SCM, explaining the mechanisms that promote or include elements in SCM and relating the elements to the basic processes of the SCOR model. Results: From the literature analysis, theoretical relations between the elements of industry 4.0 and SCM were established. An overview on the subject was provided, filling a gap in the literature. Identifying the mechanisms that promote or include elements in supply chains and the relations of elements to the SCOR model may help to guide managers for future applications of this model in a targeted manner. Limitations of the investigation: This study covers only theoretical analysis on the concepts, that is, no real applications were made considering the topics addressed. Originality/Value: The construction of a theoretical framework based on systematic literature review on SCM and Industry 4.0 is a contribution to the bibliographic database. Another contribution is the identification and analysis of the main contributions of elements to SCM in the processes of the SCOR model.